2019
DOI: 10.1016/j.rmed.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of lung disease-associated pulmonary hypertension and impact of elevated pulmonary vascular resistance

Abstract: Background: The clinical characteristics, hemodynamic changes and outcomes of lung disease-associated pulmonary hypertension (LD-PH) are poorly defined. Methods: A prospective cohort of PH patients undergoing initial hemodynamic assessment was collected, from which 51 patients with LD-PH were identified. Baseline characteristics and long-term survival were compared with 83 patients with idiopathic pulmonary arterial hypertension (iPAH). Results: Mean age ( ± standard deviation) of LD-PH patients was 64 ± 10 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This reinforces the study by A werbach et al [ 24 ], who showed in interstitial lung disease (ILD)-related PH that PVR >7 WU was associated with three-fold higher mortality than PVR <7. A werbach et al [ 24 ] also demonstrated that ILD-related PH patients, at right heart catheterisation, had lower mPAP and PVR when compared to their idiopathic pulmonary arterial hypertension (PAH) cohort; despite these findings, mortality was high in both groups.…”
Section: Pulmonary Hypertension In Interstitial Lung Diseasesupporting
confidence: 91%
See 1 more Smart Citation
“…This reinforces the study by A werbach et al [ 24 ], who showed in interstitial lung disease (ILD)-related PH that PVR >7 WU was associated with three-fold higher mortality than PVR <7. A werbach et al [ 24 ] also demonstrated that ILD-related PH patients, at right heart catheterisation, had lower mPAP and PVR when compared to their idiopathic pulmonary arterial hypertension (PAH) cohort; despite these findings, mortality was high in both groups.…”
Section: Pulmonary Hypertension In Interstitial Lung Diseasesupporting
confidence: 91%
“…This reinforces the study by Awerbach et al, who showed in ILD related PH, PVR > 7WU was associated with 3-fold higher mortality than PVR <7. Awerbach et al also demonstrated that ILD related PH patients at right heart catheterization (RHC), had lower mean pulmonary arterial pressures (mPAP) and pulmonary vascular resistance (PVR) when compared to their idiopathic PAH cohort, despite these findings, mortality was high in both groups (24).…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Rates of mortality were noted to be lower at one, two, and three years in PH-COPD compared to PH-ILD. A 2019 study comparing 51 patients with PH due to chronic lung disease to 83 patients with IPAH demonstrated that the former patient group had equally poor outcomes despite lower mean pulmonary artery pressure and pulmonary vascular resistance [31]. A PVR of seven Wood units or greater was noted to confer a 3-fold higher risk of mortality and was more strongly associated with mortality than mPAP.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Although RHC is not without risk, early RHC has demonstrated improved survival when findings have influenced management [62]. Additionally, a PVR of greater than �7 Wood Unit was found to have three times the risk of mortality in Group 3 PH patients, highlighting the prognostic value of RHC [102]. Despite common reservation, RHC should always be performed when an ILD patient is suspected to have PH and PH specific therapy is being considered.…”
Section: Hemodynamic Monitoringmentioning
confidence: 99%